Effective learning and retention of braille letter tactile discrimination skills in children with developmental dyslexia. Issue 1 (5th March 2015) - Hayek, Maisam; Dorfberger, Shoshi; Karni, Avi
Abstract: Children with developmental dyslexia (DD) may differ from typical readers in aspects other than reading. The notion of a general deficit in the ability to acquire and retain procedural ('how to') knowledge as long‐term procedural memory has been proposed. Here, we compared the ability of elementary school children, with and without reading difficulties (DD, typical readers), to improve their tactile discrimination with practice and tested the children's ability to retain the gains. Forty 10–11‐year‐olds practiced the tactile discrimination of four braille letters, presented as pairs, while blindfolded. In a trial, participants were asked to report whether the target stimuli were identical or different from each other. The structured training session consisted of six blocks of 16 trials each. Performance was re‐tested at 24 hours and two weeks post‐training. Both groups improved in speed and in accuracy. In session 1, children with DD started as significantly less accurate and were slower than the typical readers but showed rapid learning and successfully closed the gap. Only two children with DD failed to benefit from training and were not included in subsequent data analyses. At 24 hours post‐training both groups showed effective retention of the gains in speed and accuracy. Importantly, children with DD were able to retain the gains in speed and accuracy, over a two‐week interval as effectively as typical readers. Thus, children with DD were as effective in the acquisition and retention of tactile discrimination of braille letters as typical readers of the same age. The results do not support the notion of a general procedural learning disability in DD. Abstract : We report robust performance gains and skill retention after practice in a tactile braille letter discrimination task in dyslexic individuals and their typical reading peers. The figure shows group averaged braille letter discrimination time (a) and the number of errors (b) for each block in the initial training session, at 24 hours post‐training and in a test conducted two weeks post‐training. The small initial advantage of the typical readers was not apparent in the latter two time points.